2021
DOI: 10.3390/agriculture11111117
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Regionalization of Cold Resistance of Wine Grape Germplasms (V. vinifera)

Abstract: With the extreme changes of the global climate, winter freezing injury has become an important limiting factor for the development of the global grape industry. Therefore, there is a significant need for the screening of cold-resistant wine grape germplasms and cold regionalization for cold-resistant breeding and the development of grapevine cultivation in cold regions. In this study, the low-temperature half-lethal temperature (LT50) values were determined for the annual dormant branches of 124 wine grape ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
2
10
1
Order By: Relevance
“…The results showed that cold hardiness was in the order of Ecolly > Meili > Riesling > Italian Riesling > Pinot Noir > Yan73 > Viognier > Petit Manseng > Dunkelfelder > Cabernet Sauvignon > Granoir > Marselan > Ugni Blanc > Gewurztraminer > Chardonnay > Sauvignon Blanc > Syrah > Merlot > Cabernet Franc > Petit Verdot. This order is basically consistent with that of previous work to measure cold hardiness, but the measured LT 50 values are lower than other published values ( Chen et al., 2020b ; Wang et al., 2021b ). This difference may be related to specifics of our sampling location or sampling time.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results showed that cold hardiness was in the order of Ecolly > Meili > Riesling > Italian Riesling > Pinot Noir > Yan73 > Viognier > Petit Manseng > Dunkelfelder > Cabernet Sauvignon > Granoir > Marselan > Ugni Blanc > Gewurztraminer > Chardonnay > Sauvignon Blanc > Syrah > Merlot > Cabernet Franc > Petit Verdot. This order is basically consistent with that of previous work to measure cold hardiness, but the measured LT 50 values are lower than other published values ( Chen et al., 2020b ; Wang et al., 2021b ). This difference may be related to specifics of our sampling location or sampling time.…”
Section: Discussionsupporting
confidence: 92%
“…As a main cultivar, V. vinifera grapes have extremely high economic value and are used to produce grapes consumed fresh or dried or used to make wine or juice. V. vinifera varieties are often used for as starting material to generate improved varieties and as parent materials for high-quality hardiness breeding ( Wang et al., 2021b ). However, the mature shoots of V. vinifera can only tolerate a low temperature of about -15°C during winter dormancy, so in some cold regions, such as northern China and the Russian far East, soil-burial over-wintering of vines has become the main cultivation mode of V. vinifera ( Wang et al., 2021b ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations